Corporate Social Responsibility and Employees’ Performance of Companies in Kwara State - Kolawole, Kayode (Yayasan Ilomata, 2024)
The research analyzed the outcome of corporate social responsibility on employees’ performance of companies in Kwara state. The research made of primary data which was gathered through distribution of copies of questionnaire to staff of chosen companies in Kwara state. The research adopted Creswell and Creswell (2012) as the sampling technique and five hundred and seventy-six was chosen as the sample size of the research. The study employed Structural Equation Modelling using Partial Least Square (PLS) to analyzed the data acquired. The outcome of the research showed that philanthropy duty has a beneficial influence on employees’ performance in Kwara state. The research also indicated that education responsibility has a beneficial effect on employees’ performance in Kwara state. Finally, the outcome showed that ethical responsibility impacts positively on employees’ performance in Kwara state. The research determined that CSR has notable influence on employees’ performance of companies in Kwara state. The study recommends that companies should be environmentally responsible so as to enhance their employees’ performance.